Accuracy and throwing velocity in handball - Bayios, I.; Boudolos, K. (1998)
INTRODUCTION: Accuracy and throwing velocity in handball are regarded as basic parameters of performance during competition. Several investigators have studied the relationship between the velocity of movement of the upper limbs and accuracy in hitting the target, which has led to interesting theories (Schmidt, 1982, Eliasz et al., 1990, Hore, 1996). The aim of the present study was the comparative analysis of accuracy, in combination with ball velocity, while performing shots in handball, using as subjects athletes of various levels and non-athletes. METHODS: In order to measure accuracy, an innovative electronic device was used which was placed on the inner side of a goal post and functioned as a `targetpointer` (by means of a red light) and `hit-detector`. Another lab-made laser device was used for measuring ball velocity. Three groups of subjects took part in the experiments : one group of 15 handball athletes, the best of League A1 scorers (age 24.86 ± 2.91 yrs), another group of 12 handball athletes, the best of League A2 scorers (age 26.84 ± 5.67 yrs) and a random sample of 15 physical education students (21.72 ± 0.89 yrs). Accuracy and ball velocity were examined in three types of throws: (a) on the spot, (b) with a cross-over step and (c) with a vertical jump. The results were analyzed using one-way ANOVA. RESULTS: In all three types of throws examined, there was a significant difference in accuracy among groups, attributed to the higher deviation from the target observed in the student group (on the spot: Fratio= 16.422, p £ 0.001; with a crossover step: Fratio= 22.493, p £ 0.001; with an a vertical jump: Fratio= 6.825, p £ 0.003) (Table 1). Table 1 Mean values (± SD) of deviation from the target (in cm) and of ball velocity (in m/s), in the three types of throws for the three groups of subjects. With regard to throwing velocity, a significant difference among groups was found in all types of throws examined (on the spot: Fratio= 54.585, p £ 0.001; with a crossover step: Fratio= 33.578, p £ 0.001; with an a vertical jump: Fratio= 20.795, p £ 0.001), which was attributable to the fact that all three groups differed significantly from each other. In the throw with a vertical jump the difference between the two groups of athletes was less than that observed in the other two types of throw. This was probably due to the advanced technical skill required for performing this type of throw. CONCLUSIONS: The throwing performance of the three groups of subjects was assessed both by the level of accuracy and the magnitude of ball velocity in their throws. The performance of the best scores in the League A1 group significantly exceeded that of the other groups for the variables studied in the three types of throwing examined by the present study.